2022
DOI: 10.1101/2022.01.10.475632
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Amniotic fluid stem cell extracellular vesicles promote fetal lung branching and cell differentiation in experimental congenital diaphragmatic hernia

Abstract: Pulmonary hypoplasia secondary to congenital diaphragmatic hernia (CDH) is characterized by impaired branching morphogenesis and differentiation. We have previously demonstrated that administration of extracellular vesicles derived from rat amniotic fluid stem cells (AFSC-EVs) rescues development of hypoplastic lungs at the pseudoglandular and alveolar stages in rodent models of CDH. Herein, we tested whether AFSC-EVs exert their regenerative effects at the canalicular and saccular stages, as these are transla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
11
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(14 citation statements)
references
References 64 publications
2
11
1
Order By: Relevance
“…As they typically appear during the canalicular stage, we evaluated the expression of lipofibroblast markers at the canalicular, saccular, and alveolar stages. We confirmed that fetal hypoplastic lungs had reduced density of lipofibroblasts at all these stages of lung development, and that AFSC‐EV administration rescued their expression to control levels 29,64 …”
Section: Administration Of Afsc‐evs Rescues Lung Growth and Maturationsupporting
confidence: 65%
See 4 more Smart Citations
“…As they typically appear during the canalicular stage, we evaluated the expression of lipofibroblast markers at the canalicular, saccular, and alveolar stages. We confirmed that fetal hypoplastic lungs had reduced density of lipofibroblasts at all these stages of lung development, and that AFSC‐EV administration rescued their expression to control levels 29,64 …”
Section: Administration Of Afsc‐evs Rescues Lung Growth and Maturationsupporting
confidence: 65%
“…64 Specifically, we observed an increase in number of branches and airspaces, as well as a rescue of expression levels of genes involved in branching morphogenesis. 64 When we assessed the last stage of lung development, we found that the lungs of fetal rabbit pups treated with AFSC-EVs had a restored number of alveoli and decreased alveolar thickness, as well as normalized levels of BMP signaling (BMP, BMP2, BMP4, and Id1), a critical pathway for alveolarization. 29 Next, we evaluated the effects of AFSC-EVs on lung epithelial maturation.…”
Section: Administration Of Afsc-evs Rescues Lung Growth and Maturationmentioning
confidence: 70%
See 3 more Smart Citations